Chemically Locked Bicelles with High Thermal and Kinetic Stability. Issue 45 (16th September 2015) - Matsui, Ryoichi; Ohtani, Masataka; Yamada, Kuniyo; Hikima, Takaaki; Takata, Masaki; Nakamura, Takashi; Koshino, Hiroyuki; Ishida, Yasuhiro; Aida, Takuzo
Abstract: In situ polymerization of a bicellar mixture composed of a phospholipid and polymerizable surfactants afforded unprecedented stable bicelles. The polymerized composite showed an aligned phase over a wide thermal range (25 to >90 °C) with excellent 2 H quadrupole splitting of the solvent signal, thus implying versatility as an alignment medium for NMR studies. Crosslinking of the surfactants also brought favorable effects on the kinetic stability and alignment morphology of the bicelles. This system could thus offer a new class of scaffolds for biomembrane models. Abstract : Link and lock: In situ polymerization of a bicellar mixture composed of a phospholipid and polymerizable surfactants afforded unprecedented stable bicelles. The polymerized composite showed an aligned phase over a wide thermal range with excellent 2 H quadrupole splitting of the solvent signal, thus suggesting utility as an alignment medium for NMR studies. The crosslinking also notably improved the kinetic stability and alignment morphology of the bicelles.